Fermentos y tiempos de fermentación en la elaboración de vino de borojó (Borojoa patinoi). Quevedo – Los Ríos. 121 p. - Guerra Macías, Pablo Antonio (2014)
This research was conducted at the Experimental Farm "La María" at Universidad Técnica Estatal of Quevedo, in the Nutritional Science laboratory of Animal science Faculty, located at Km 71/2 via Quevedo - El Empalme, in Los Rios province. The following objectives were posed: 1) Assess the wine yeast (S. cerevisiae bayanus) and Levapan baker's yeast (S. cerevisiae); 2) Evaluate borojó wine at 10, 15, 20 days of fermentation; 3) Set the benefits and cost of treatments. A Bifactorial setting of 2x3 was apply in a completely randomized design with three repetitions. Two types of yeast were used (wine yeast and baker's yeast) and three fermentation lapses (10, 15 and 20 days), obtaining a total of six interactions. Tukey's test was used for measure comparison (p≤ 0.05). The variables showed significant statistical difference; ° Brix, present values of 6.00 - 6.50 for yeast bread and the wine yeast 6.00 - 6.43, the pH values of 2.93 - 2.99 in yeast bread, and the wine yeast 2.92 - 2.97; the acidity present values from 0.49 to 0.52 and 0.48 to 0.52, and the alcoholic degree variable values were 10.92 - 12.58 and wine yeast 10.83 - 12.75. Regarding Organoleptic wine analysis presents; slight smell of borojo but much more of alcohol, coloration was lighter than borojo, high taste of borojo and alcohol. Through economic analysis, the B/C wine borojo relation was determined; issuing a value of $1.33 for wine yeast and yeast, profitability of 33.25% for yeast bread and 33.30% for wine yeast, and a production of 59.48% in winemaking.